Kepuasan Wisatawan : Tinjauan Terhadap Atraksi, Aktivitas, Amenitas dan Aksesibilitas Di Taman Nusa Bali - Dyah Palupiningtyas; Heru Yulianto (STEKOM PRESS, 2018)
This study aims to analyze and explain the influence of Attractions, Activities, Amenities, and Accessibility (4A) on tourist satisfaction at Taman Nusa Bali which is experiencing unfavorable conditions including a decrease in the level of tourist visits every year, besides that there are several conditions of tourism components that need to be improved. The sample used in the study was 100 respondents. The research data was processed by quantitative statistical analysis using multiple regression analysis to determine the effect of the independent variable on the dependent variable. The results of the regression analysis show that an increase in variable 4A will increase tourist satisfaction. The results of the multiple regression analysis test show a significant F value, the adjusted R2 square coefficient value of 0.604 indicates that all 4A variables have a significant effect on tourist satisfaction together with a close relationship of 60.4%. This shows that to increase tourist satisfaction it is necessary to increase all tourism components in order to increase tourist satisfaction in the next period.